Violations of the Village Endogamy Marriage Tradition in Tenganan Pegringsingan Karangasem Bali - Murtini, Ni Kadek; Sukarlinawati, Wayan (International Journal of Multidisciplinary Sciences, 2024)
The existence of Tenganan Village as a Bali Aga Village has its own uniqueness compared to other areas in Bali, one of which lies in its marriage system. The ideal marriage system in the Tenganan Pegringsingan community is family exogamy or village endogamy. Regarding the marriage system governed by the traditional village regulations (awig-awig), many violations have been committed by the members of the Tenganan Pegringsingan Traditional Village, which poses a threat to the continuity of the customs and traditions of the village in the future. The objectives of this study are: to identify the causes of violations of the village endogamy marriage system in the Tenganan Pegringsingan Traditional Village, to understand the process of imposing sanctions on residents who violate this system, and to analyse the implications of these sanctions on the status and roles of the offenders within the village. This article uses a qualitative approach to gather data from various sources relevant to the research needs. Interviews with community leaders from the Tenganan Pegringsingan Traditional Village revealed that the causes of violations of the village endogamy marriage system are psychological and environmental factors. Violations of the awig-awig result in the following sanctions: exclusion from the village's communal activities (mekrama), relocation to Banjar Pande, and fines imposed on the violators' parents. The implications include differences in status and roles within the community. Residents who are not members of the krama desa adat (traditional village community) lose their rights within the traditional village. The uniqueness of the Tenganan Pegringsingan Traditional Village, which sets it apart from other villages in Bali, deserves attention from policymakers to ensure that the traditional values and cultural heritage of the village are preserved.